Logic programming, knowledge representation, and nonmonotonic reasoning essays dedicated to Michael Gelfond on the occasion of his 65th Birthday - Son, Tran Cao; Balduccini, Marcello (Lecture Notes in Computer Science, 2011)
This Festschrift volume, published in honor of Michael Gelfond on the occasion of his 65th birthday, contains a collection of papers written by his closest friends and colleagues. Several of these papers were presented during the Symposium on Constructive Mathematics in Computer Science, held in Lexington, KY, USA on October 25-26, 2010. The 27 scientific papers included in the book focus on answer set programming. The papers are organized in sections named Foundations- ASP and Theories of LP, KR, and NMR, ASP and Dynamic Domains, and ASP Applications and Tools.